ANALISIS FKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KONDILOMA AKUMINATA DI POLIKLINIK KULIT DAN KELAMIN RSUD Dr. H. ABDUL MOELOEK BANDAR LAMPUNG TAHUN 2016 - Djunizar Djamaludin; Yuyun Tyas; Eka Trismiyana (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2019)
ABSTRACT : MUSCULOSKELETAL DISORDERS IN THE WORKPLACE AMONG NURSES AT ZAINAL ABIDIN PAGARALAM HOSPITAL WAY KANAN Background: Lower back pain is one of the occupational diseases that often occur to nurses in hospitals, especially in the inpatient unit; Due to the nature of the work which is very heavy, with bending and twisting movements of the body, especially around the lower spine. Results from Pre survey on 10 nurses in the adult ward at Zainal Abidin Pagaralam’s Hospital Way Kanan, 6 nurses (60%) had complains low back pain and needs to do physiotherapy, and 4 nurses reported the limited hospital facilities.Purpose : Knowing that correlation between musculoskeletal disorders and the workplace among nurses at Zainal Abidin Pagaralam Hospital Way Kanan Province Of Lampung 2018.Methods : This type of research is quantitative, with cross sectional design. The total sample is all nurses that is 72 respondents. The instrument of this study is a questionnaire with statistical test using Chi square test.Results: Finding 45 (62.5%) of respondents said a good working environment, whereas 27 (37.5%) of respondents expressed unfavorable working environment. 41 (56.9%) of respondents complained Musculosceletal Disorder moderate, and 31 (43.1%) of respondents complained Musculosceletal heavy Disorder, with a p-value 0.000 and the value of OR 10 818.Conclusion : There is correlation between musculoskeletal disorders and the workplace among nurses at Zainal Abidin Pagaralam Hospital Way Kanan Province Of Lampung 2018. It is suggested that the hospital management can reduce complaints Musculosceletal Disorder by maintaining a good working environment.Keywords : Workplace, musculoskeletal disorders, nursesPendahuluan : Nyeri punggung bawah merupakan salah satu penyakit akibat kerja yang sering terjadi pada perawat di rumah sakit, terutama di ruang rawat inap; karena sifat pekerjaannya yang banyak mengangkat beban pasien dewasa yang berat, dengan gerakan membungkuk dan memutar tubuh, khususnya sekitar tulang punggung bawah. Hasil Prasurvey dari 10 perawat di ruang rawat inap dewasa RSUD Zainal Abidin Pagaralam Way Kanan, 6 (60%) perawat pernah mengalami keluhan nyeri punggung bawah hingga melakukan fisioterapi, dan 4 (40%) perawat melaporkan banyaknya keterbatasan fasilitas rumah sakit.Tujuan: Diketahui Hubungan lingkungan kerja dengan kejadian musculoskeletal disoders pada perawat di RSUD Zainal Abidin Pagaralam Way Kanan Tahun 2018.Metode : Jenis penelitian ini kuantitatif, dengan design cross sectional. Jumlah sampel adalah seluruh perawat yaitu 72 responden. Instrument penelitian ini kuisioner dengan uji statistic menggunakan uji Chi square.Hasil : Didapatkan 45 (62.5%) responden menyatakan lingkungan kerja baik, sedangkan 27 (37.5%) responden menyatakan lingkungan kerja kurang baik. 41 (56.9%) responden mengeluh Musculosceletal Disorder sedang, dan 31 responden (43.1%) mengeluh Musculosceletal Disorder berat, dengan nilai p-value 0.000 dan nilai OR 10.818.Simpulan : Ada hubungan lingkungan kerja dengan kejadian muskuloskeletal disorders pada perawat di Rumah Sakit Umum Daerah Zainal Abidin Pagaralam Way Kanan Tahun 2018. Disarankan kepada manajemen rumah sakit dapat mengurangi keluhan Musculosceletal Disorder dengan cara mempertahankan lingkungan kerja yang baik.